IMPROVEMENT OF DIPOLE ANTENNA GAIN USING 8 CBU AMC-EBG AND 8 CBU FSS - Abu, Maisarah; md. ali, siti Adlina; Zabri, S.N. (2017)
This paper investigates the performances of dipole antenna incorporated with and without 8 CBU AMC-EBG and 8 CBU FSS at 5.8 GHz. The designs are simulated on Rogers RO 3010. Due to the flexibility of the material used as a substrate, the effect of a different angle is investigated. Both 8 CBU AMC-EBG and 8 CBU FSS act as reasonably good ground plane for the dipole antenna and help improving the realised gain and improve the radiation patterns by push the front lobe at the same time reduce the side lobes. The maximum improvements led by dipole antenna with 8 CBU AMC-EBG thus 8.543 dB of realised gain achieved and the front lobe is pushed higher and the side lobe is significantly lowered than with 8 CBU FSS. The designs of dipole antenna with 8 CBU AMC-EBG and 8 CBU FSS can be applied as high gain atenna for Intelligent Transport System (ITS).